Thiopurine S-methyltransferase genetic polymorphisms in adult patients with inflammatory bowel diseases in the Latvian population. (July 2020) - Zalizko, Polina; Stefanovics, Juris; Sokolovska, Jelizaveta; Paramonova, Natalia; Klavina, Evija; Erts, Renars; Rovite, Vita; Klovins, Janis; Pukitis, Aldis
Background: Thiopurine methyltransferase (TPMT) plays a significant role in the metabolism of thiopurines, and, for patients with inflammatory bowel disease (IBD), it is useful to perform TPMT genotyping prior to azathioprine (AZA) treatment. In this study, we determined TPMT gene polymorphisms in a cohort of IBD patients in Latvia. Methods: DNA samples were obtained from 244 IBD patients, and qPCR was performed for detection of rs1800462, rs1800460, and rs1142345 single-nucleotide polymorphisms (SNPs). Three common, non-functional TPMT alleles ( TPMT*2, *3B, and *3C ) were identified (women, 51%; men, 49%). TPMT*2, *3A, *3B, and *3C allelic variants detected using qPCR were consistent with restriction fragment length polymorphism (RFLP) data. Results: Among patients, 78% had ulcerative colitis and 22% had Crohn's disease, with 93.9% of the former carrying a wild-type homozygous TPMT*1/*1 genotype and 6.1% carrying heterozygous genotypes. The most frequent polymorphisms were TPMT*1/*3A (5.3%: two variants: TPMT*3B and TPMT*3C ), TPMT*1/*3C (0.4%), and TPMT*1/*2 (0.4%). None of the patients carried a TPMT*3B polymorphism and no patients were homozygous for any mutation. Conclusion: This is the first study to identify TPMT gene polymorphisms in adult IBD patients in Latvia. The results indicate that the frequency of common TPMT alleles is similar to that of other European populations.